Ad-Du’ât‘Inda Sa’îd Hawwa fi al-Asâs fi Tafsîr - Mujib Abdurrahman; Putri Rahmawati (Studia Quranika, 2018)
This paper discusses about the term da’i in Qur'an, which is one of the discussions that are often discussed by religious leaders lately, both in terms of meaning and tafseer. Sa'id Hawwa is one of the famous da’i and activist of da’wah an important role in the da’wah movement of the Muslim Brotherhood, so he was more focused on study about da’i in his tafseer. Sa'id Hawwa explains the term da’i has various meaning according to the context of the verse. Prophet Muhammad is a messenger called by God as a da’i, so is prophet before prophet Muhammad. In other words, the whole of the Prophet is a da’i. And the Prophet Muhammad is the greates da’i for Muslims, and God exalted the umma of Muhammad to become a da’i.